ANALYSIS OF FACTOR ASSOCIATED WITH UTERINE MYOMA INCIDENCE AT BHAYANGKARA HOSPITAL KEDIRI - Heni Purwati (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2026)
Uterine myoma is a common benign tumor of the uterus in women of reproductive age and is frequently diagnosed in advanced stages when the tumor has reached a considerable size. This study aimed to analyze the dominant factor associated with uterine myoma incidence based on age, parity, and occupation among patients at Bhayangkara Hospital Kediri in 2025. This quantitative study used a cross-sectional design involving 92 medical records selected through purposive sampling. Data were analyzed using Chi-Square test and simple logistic regression. The results showed that most respondents were aged >35 years (88%), multiparous (79.3%), and housewives (59.8%). The Chi-Square test indicated a significant relationship between age and uterine myoma incidence (p = 0.000). Logistic regression analysis revealed that age >35 years was the dominant factor influencing uterine myoma incidence with an odds ratio (OR) of 124.5 (p = 0.000), while parity (p = 0.312) and occupation (p = 0.487) were not statistically significant. In conclusion, age is the most dominant factor associated with uterine myoma incidence, while parity and occupation are not significant predictors. Early screening for women aged over 35 years is strongly recommended